Pengaruh Kualitas Produk, Harga dan Lokasi terhadap Keputusan Pembelian Mie Ayam Raja Sugiarto di Solo - Aprilliya Galuh Pratiwi; Sumaryanto Sumaryanto (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine the effect of product quality, price, and location on purchasing decisions on raja sugiarto chicken noodles in Solo. The type of data used in this study is quantitative data, the data source used is primary data. The population in this study were consumers of raja sugiarto chicken noodles located on Jl. K.H Samanhudi No.73, Purwosari, Laweyan, Solo. The sample used in this study was non probability sampling with accidental sampling technique with a sample size of 100 respondents. The data collection technique used a questionnaire. The data analysis technique used is descriptive analysis, multiple linear regression analysis, t test, F test, R2 test. The results of this study indicate that product quality has a significant effect on purchasing decisions on raja sugiarto chicken noodles in Solo, with a sig value of 0.000 < 0.05. Price has no significant effect on purchasing decisions on raja sugiarto chicken noodles in Solo, with a sig value of 0.250 <0.05. Location has a significant effect on purchasing decisions on raja sugiarto chicken noodles in Solo, with a sig value of 0.000 < 0.05.